2022
DOI: 10.2166/wp.2022.252
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a water resource tax policy in improving water-use efficiency: a quasi-natural experiment-based approach

Abstract: Comprehensively improving the efficiency of water resource utilization is not only an urgent need to resolve the prominent contradiction between water supply and water demand but also an inevitable requirement to promote the harmonious coexistence between humans and nature. The compulsory water resource tax is considered to be a powerful tool for resolving the worldwide water crisis and improving water resource utilization efficiency (WRUE). Based on a quasi-natural experiment of water resource tax policy in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Computable general equilibrium model [ 8 ], (progressive) double difference method [ 10 ], general equilibrium model [ 11 ], synthetic control method [ 9 ], multiple regression model [ 10 , 12 , 13 ], and other research methods have been applied to quantitatively portray the implementation effect of water tax policy and its influencing factors. Specifically, the effectiveness of water resource tax reform was evaluated in terms of water use efficiency [ 10 ], reduction of negative resource externalities [ 9 ], amount of profits and taxes [ 8 , 13 ]. In addition, the direct and indirect impacts of policy changes on all aspects of society are explored from the impact of water resources tax on water use, production and trade patterns, and the scale of welfare losses [ 11 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Computable general equilibrium model [ 8 ], (progressive) double difference method [ 10 ], general equilibrium model [ 11 ], synthetic control method [ 9 ], multiple regression model [ 10 , 12 , 13 ], and other research methods have been applied to quantitatively portray the implementation effect of water tax policy and its influencing factors. Specifically, the effectiveness of water resource tax reform was evaluated in terms of water use efficiency [ 10 ], reduction of negative resource externalities [ 9 ], amount of profits and taxes [ 8 , 13 ]. In addition, the direct and indirect impacts of policy changes on all aspects of society are explored from the impact of water resources tax on water use, production and trade patterns, and the scale of welfare losses [ 11 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing studies have shown that the implementation effect of water resources tax is significantly affected by various factors, and there is spatial heterogeneity [ 10 ]. Technological progress [ 14 ], water resource endowment [ 15 ], regional economic development level [ 14 ], acreage and fertilizer use [ 16 ] all had a significant impact on the implementation effect of water resources tax.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It can be innovative development, accelerate the process of enterprises to complete the introduction of water-saving technology facilities, promote the optimization and upgrading of industrial structure, and improve the utilization efficiency and use-value of water resources. The water resources tax absorbs the profits of enterprises and supplements the ecological environment, which ensures the recovery of water resources recycling capacity and the improvement of water supply capacity under the condition of increasing water demand and realizes the dual goals of sustainable economic development and sustainable use of water resources [67]. The internal relationship of water resources tax policy effect is shown in Fig 7.…”
Section: Plos Onementioning
confidence: 99%
“…Ref. [18] point out that the water resources tax has increased the tax burden of urban water supply enterprises. Ref.…”
Section: Introductionmentioning
confidence: 99%